Migration governance in the Global South: a comparative analysis - María del Carmen Villarreal Villamar; Adriana Montenegro Braz (Revista CIDOB d'Afers Internacionals)
This paper examines the characteristics of migration governance in the Global South with a view to identifying whether it has distinctive features compared to the Global North and whether those differences can be considered contributions to the migration debate on the part of the South. It studies migration patterns in Africa, Asia and Latin America, as well as the actors, trends and governance practices involved. The analysis reveals that the hegemonic migration governance agenda also exists in the Global South, and its implementation has taken on a more restrictive and securitised nature, particularly since the COVID-19 pandemic. Its implementation, however, is marked by disputes and peculiarities that are coloured by factors such as intraregional migration, pre-existing regional integration agreements and free movement frameworks, as well as processes of resistance and the construction of alternative forms of governance on the part of various actors.